PELATIHAN PEMBELAJARAN BAHASA ARAB BERBASIS E-LEARNING DI MADRASAH IBTIDAIYAH MIFTAHUL KHAIR BANJARMASIN - Try Viananda Nova M; Rina Alfah; Ibrahim Ibrahim (Universitas Islam kalimantan MAB, 2018)
Our Action are to Introduce and provide other skills and benefits of E-Learning Arabic language subjects to students from Madrasah Ibtidaiyah Miftahul Khair Banjarmasin and teachers also to let them know that E- Learning is one of the solutions to provide creative and innovative lessons and to increase children's interest in Arabic subjects. This activity aims to introduce and give lessons to students / students and teachers of Madrasah ibtidaiyah miftahul khair using E-Learning media subjects Arabic language for students to be eager in receiving lessons Especially subjects of Arabic and teachers are more skilled and can apply the modern way of teaching using the media.